2014
DOI: 10.3748/wjg.v20.i18.5263
|View full text |Cite
|
Sign up to set email alerts
|

Vacuoles of Candida yeast as a specialized niche forHelicobacter pylori

Abstract: Helicobacter pylori (H. pylori) are resistant to hostile gastric environments and antibiotic therapy, reflecting the possibility that they are protected by an ecological niche, such as inside the vacuoles of human epithelial and immune cells. Candida yeast may also provide such an alternative niche, as fluorescently labeled H. pylori were observed as fast-moving and viable bacterium-like bodies inside the vacuoles of gastric, oral, vaginal and foodborne Candida yeasts. In addition, H. pylori-specific genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(94 citation statements)
references
References 92 publications
1
93
0
Order By: Relevance
“…Subjects with abundant H pylori in the stomach have significantly different duodenal and oral (both oral and tongue) communities when compared to H pylori negative individuals . One study showed that healthy H pylori positive individuals have reduced oral microbiota diversity, relatively more Proteobacteria and less Fusobacteria and Firmicutes than H pylori negative individuals . Similarly, the presence of H pylori in the stomach of gastritis patients was associated with modest changes in the tongue coating microbiota, while these changes were more pronounced if the H pylori strain was cytotoxin‐associated gene A‐positive …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with abundant H pylori in the stomach have significantly different duodenal and oral (both oral and tongue) communities when compared to H pylori negative individuals . One study showed that healthy H pylori positive individuals have reduced oral microbiota diversity, relatively more Proteobacteria and less Fusobacteria and Firmicutes than H pylori negative individuals . Similarly, the presence of H pylori in the stomach of gastritis patients was associated with modest changes in the tongue coating microbiota, while these changes were more pronounced if the H pylori strain was cytotoxin‐associated gene A‐positive …”
Section: Resultsmentioning
confidence: 99%
“…In this study, amplification of ITS from gastric RNA failed on all 50 analysed samples indicating that yeasts do not appear to be metabolically active in the gastric environment. However, yeasts may have a particular role in facilitating survival of bacteria as endosymbiotic relationships between bacteria and yeasts has been shown including in the case of H pylori and Candida . Furthermore, fungal colonisation of the stomach appears to be more common among patients suffering from gastric ulcer or gastritis than healthy subjects …”
Section: Introductionmentioning
confidence: 99%
“…isolated from the oral cavity of dyspeptic patients were found to contain bacteria-like bodies inside their vacuoles. These contained H. pylori -specific 16S rRNA and H. pylori proteins such as urease, vacuolating toxin (VacA), periredoxin and thiolperoxidase [67]. Fluorescence microscopy revealed H. pylori cells inside the mildly-acidic vacuoles of mother and daughter cells, suggesting that the endobacteria could multiply and transmit.…”
Section: A Mushrooming Fieldmentioning
confidence: 99%
“…18 This relationship may allow H pylori to colonize the vagina. Candida isolated from the vagina has been found to contain H pylori specific genes, one mechanism for the vertical transmission of H pylori.…”
Section: Bacterial Vaginosis and Helicobacter Pylori Infectionmentioning
confidence: 99%